The Dakar Bus Renewal Scheme : Before and After - Kumar, Ajay (World Bank, Washington, DC, 2014)
The population of Senegal is about 12 million. Over 3 million people live in the Dakar metropolitan region, which is growing at twice the pace of the country as a whole (the population growth rate of Dakar is about 3.6 percent per year compared with the national rate of 2.2 percent per year). As in most cities in developing countries, authorities have found it difficult to meet the service demands of the growing population, particularly those of the poor, who are the most dependent on the public provision of water, electricity, transport, and other services. The objective of this study is to (1) establish how effective the finance scheme has been in improving the quality of urban transport services in Dakar since its implementation in 2005; (2) examine whether the approach is proving to be financially self-sustaining and what effect the introduction of new vehicles is having on other service providers; and (3) determine whether, on the basis of the available evidence, the scheme offers a sustainable approach (both operationally and financially) to improving transport service provision in other Sub-Saharan Africa (SSA) cities. The program is not designed to increase public transport capacity, and thus the impact on other transport operators has been minimal. Service quality has improved to the satisfaction of the general public.